Pengaruh Inovasi Produk, Literasi Keuangan, dan Akses Pembiayaan terhadap Pertumbuhan UMKM di Indonesia - Antoni, Antoni; Karlin, Karlin (Westscience Press, 2024)
This study investigates the impact of product innovation, financial literacy, and access to financing on the growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. A quantitative approach was employed, involving 180 MSME owners and managers. Data were collected through a structured questionnaire using a 5-point Likert scale, and the analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that all three factors—product innovation, financial literacy, and access to financing—positively and significantly influence MSME growth, with product innovation having the strongest effect. These findings highlight the importance of fostering innovation, enhancing financial literacy, and improving access to financing as key strategies for promoting MSME growth. The study offers valuable insights for policymakers and business practitioners to support MSMEs' sustainability and competitiveness in emerging markets like Indonesia.